Mechanical properties of kenaf fibre reinforced floreon biocomposites with magnesium hydroxide filler - C.H. Lee; S.M. Sapuan; J.H. Lee; M.R. Hassan (Journal of Mechanical Engineering and Sciences, 2016)
This paper presents a study of the mechanical properties of Kenaf fibre (KF) reinforced floreon (FLO)/ magnesium hydroxide (MH) bio-composites. The mixing of all materials was done by using a 21 mm lab twin screw extruder followed by hot pressing. The composite sheet was then cut into specimens for testing purposes. The scanning electron microscopy (SEM) was used to study the cross-section of the interface. In this regard, insufficient resin for fibre wetting, hydrolytic degradation on the biopolymer and poor interfacial bonding were attributed to the low strength profile. Yet, further addition of KF increased the tensile strength and flexural to 18.91 MPa and 73.09MPa, respectively. Nevertheless, inserting KF and MH filler were found to have a positive outcome on the flexural modulus by especially 10KF5MH and 10KF10MH for 3.02GPa and 3.17GPa, respectively. Insertion of KF and MH showed the deterioration of impact strength. However, addition of KF increased the impact strength to 16.82 J/m2. FLO is a hydrophobic biopolymer, and showed only 0.49% of the total water absorption in 14 days. Meanwhile, for the first 24 hours, the rates of water absorption were very high for all bio-composites. Hence, it is worth mentioning that the high contents of KF in bio-composites were found to have higher saturation period and higher total amount of water absorption while the MH caused shorter saturation period but lower total amount of water absorption. However, incompatibility of the interface bonding had increased the water absorption of KF/FLO/MH composites. 5KF5MH and 10KF5MH recorded water absorption at 10.65% and 13.33%. On the other hand, 10KF10MH was saturated at day 6 with 6.59 % of water absorption. Although 10KF5MH specimen did not have the best performance in mechanical properties, higher flame retardancy shall provide KF reinforced FLO composite with MH filler for more applications in the advanced sector, especially a hazardous environment.